Minimal encephalopathy in hereditary hemorrhagic telangiectasia patients with portosystemic vascular malformations - B. Villanueva; A. Cañabate; R. Torres-Iglesias; P. Cerdà; E. Gamundí; Q. Ordi; E. Alba; L. A. Sanz-Astier; A. Iriarte; J. Ribas; J. Castellote; X. Pintó; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Hereditary hemorrhagic telangiectasia (HHT) is characterized by telangiectasia and larger vascular malformations. Liver malformations are the most frequent visceral involvement including the presence of portosystemic malformations (PSM) that can cause hepatic encephalopathy. Minimal hepatic encephalopathy (mHE) is characterized by alterations of brain function in neuropsychological or neurophysiological tests and decreases quality of life. The evidence of mHE in HHT patients is scarce. The aim of this study is to assess the prevalence and health impact of mHE in patients with and without PSM. Methods We performed a cross-sectional observational study in a cohort of patients from an HHT referral unit. Adult patients with definite HHT and PSM and age and sex matched HHT controls without PSM (1:1) were included. Baseline clinical, imaging and laboratory tests and different neuropsychological tests for the screening of mHE were compared between both groups. Results Eighteen patients with PSM and 18 controls out of 430 HHT patients were included. Patients with PSM showed higher prevalence of attention disturbances (50% vs. 11.1%, p = 0.027), falls during last 12 months (22.2% vs. 5.6%, p = 0.338), sleep disorders (50% vs. 16.7%, p = 0.075) and a worst performance in s-ANT1 test (14 vs. 19.5 points score, p = 0.739) than HHT controls. Conclusions HHT patients with PSM showed higher attention difficulties than HHT controls, though both PSM and HHT controls showed findings of mHE. Specific neuropsychological tests for early detection of mHE should be considered in HHT patients.